Peasant Understanding of Food Sovereignty: Indonesian Peasants in a Transnational Agrarian Movement - Seminar, Annisa; Sarwoprasodjo, Sarwiti; Kinseng, Rilus (Makara Human Behavior Studies in Asia, 2018)
La Via Campesina (LVC) is atransnational agrarian movement that actively promotes food sovereignty as analternative approach to the global food crisis. Communication among local,national, and global members of this movement is needed to spread it furtherand support food sovereignty. This study focused examines the dynamics of local–globalcommunication in a food-sovereignty movement by comparing peasants’ statementsin the relevant communicative spaces and official texts produced by LVC. Themethod of ethnography of communication (EO) is used to determine peasants’ understandingof food sovereignty and the context that influences it. Based on a multi-sitestrategy of ethnography for gathering data, we observed seven relevantcommunicative spaces and interviewed 22 peasants from 15 Indonesian regions. Wealso gathered secondary data to analyze LVC’s official publications. We found aconvergence between local and global in understanding food sovereignty, suggestingthat the dynamics of local–global communication are influenced by the following:(1) the existence of communicative spaces on the local, national, and global levels;(2) the importance of the participation of local peasants in thesecommunicative spaces; and (3) location-specific issues.